JIGSAW LEARNING STRATEGY IN A DIVERSE SCIENCE-CLASSROOM SETTING: FEASIBILITY, CHALLENGES, AND ADJUSTMENT - Muhammad Haris Effendi Hasibuan; Fuldiaratman Fuldiaratman; Fatria Dewi; Urip Sulistiyo; Susi Hindarti (Jurnal Cakrawala Pendidikan, 2020)
Jigsaw learning strategy is considered effective in enhancing students’ learning outcomes. Yet, it is problematic for a science classroom that contains educational challenges. The aim of this study was to investigate the implementation of the jigsaw learning in science classes in Indonesian classrooms. This included the feasibility of the jigsaw strategy, the challenges that interfered with the implementations, and the necessary approach to fit the strategy with the challenges. A qualitative case study was used. Three chemistry classes (each consisted of 35 grade 11 students) and a chemistry teacher were involved in this study. Data were collected from classroom observations and interviews. The findings showed that jigsaw learning was not fully feasible as it could not be completely implemented in the participating classes. Unsupportive educational settings such as time limitation, large population, the ill-sized classroom, teacher’s lack of participation and the complexity of the jigsaw structure had influenced the lack of success of the implementations. Rather than seeking help from educational supports that normally involves a financial-concern educational policy, this study recommends adjusting the jigsaw structure to increase its feasibility in such learning condition.